Review on processes and management of saltmarshes across Great Britain - Cai Ladd (Proceedings of the Geologists' Association, 2021)
Centuries of coastal development has led to the loss of saltmarsh extent worldwide. As marshes are shrinking, scientific understanding of marsh expansion and erosion processes is growing. Coastal managers are also recognising the importance of marshes for flood protection, carbon sequestration, and pollutant filtering. Considerable effort is now being made to conserve saltmarshes. However, the rapid integration of science in policy remains an obstacle for ensuring successful conservation outcomes. This review explores how advances in the understanding of coastal dynamics, and the evolution of coastal management thinking, are shaping saltmarsh conservation policy in Great Britain. Saltmarsh management has shifted from reclamation, to protection, to restoration throughout the 20th and 21st centuries as calls for nature conservation grew and the importance of ecosystems in coastal erosion risk management became apparent. Studies have revealed that marshes cycle between expansion and erosion phases as part of their natural evolution, governed by processes acting across a range of spatial and temporal scales. Understanding which processes drive long-term marsh change provides an opportunity for coastal managers to undertake targeted intervention for positive conservation outcomes. The inherently dynamic nature of marshes also raises significant challenges in forecasting the long-term value provided by a given marsh. Challenges remain in the monitoring and management of sediment supply and transport, and the effective engagement with stakeholders during habitat protection and creation schemes, which are key to achieving marsh conservation goals.